Surveillance for Healthcare-Associated Influenza-Like Illness in Pediatric Clinics: Validity of Diagnosis Codes for Case Identification. (15th July 2016) - Feemster, Kristen A.; Odeniyi, Folasade M.; Localio, Russell; Grundmeier, Robert W.; Coffin, Susan E.; Metlay, Joshua P.
Abstract : Compared to chart review, a definition based on the International Classification of Disease, Ninth Revision, Clinical Modification (ICD-9-CM) diagnosis code for healthcare-associated influenza-like illness (HA-ILI) among young children in a large pediatric network demonstrated high positive and negative predictive values. This finding suggests that electronic health record–based definitions for surveillance can accurately identify medically attended outpatient HA-ILI cases for research and surveillance. Infect Control Hosp Epidemiol 2016;1–4